Penguatan Ketahanan Pangan bagi Masyarakat Terdampak Covid-19 - Fandi Fatoni; Ulil Hartono; Anang Kistyanto; Musdholifah; Yuyun Isbanah (Inspirasi Nusantara, 2021)
The city of Surabaya is the city with the second highest number of people affected by the Covid-19 virus after DKI Jakarta. Surabaya is the center for administrative service activities, offices, services, shopping, industry and other supporting sectors. With the Covid-19 virus pandemic spreading so fast, the Surabaya City government issued regulations for working at home, studying at home, and limiting activities that led to large gatherings of people. Problems arise when the activities of schools, agencies, offices, motorcycle taxis, and some informal workers are economically affected. As well as government regulations that must be obeyed in overcoming the Covid-19 pandemic, it also needs to be understood. This community service has a target, namely increasing food security, especially in terms of meeting basic needs. The implementer understands that in terms of meeting their basic needs, they have a few problems related to how to get it due to the large-scale social restrictions (PSBB), the distribution of PKM funds as foodstuffs is carried out in order to meet the basic food needs of the people affected by Covid-19 so that it can support public welfare. The method used is data collection of students and contract workers / utsourcing affected by Covid 19 who survive in boarding houses around the UNESA Ketintang campus location and distribution of nutrition and immunity enhancing food ingredients. As a result, there were 35 packages distributed to management students and non-contract / outsourcing FE Unesa who were affected by Covid 19 to meet food needs. Recipients of basic food packages consider that the packages are very important to meet food needs and maintain body resistance so that they are not susceptible to disease